Comparing the Effect of Teaching Breast Self-Examination by Peers and Health Care Personnel on Students Knowledge and Attitude - Marzieh Akbarzadeh; Mahdieh Zangiabadi; Marzieh Moattari; Hamidreza Tabatabaei (مجله ایرانی آموزش در علوم پزشکی, 2009)
Introduction: Training breast self-examination by peers provides an appropriate situation in order to form proper health behaviors during the adolescence age. The aim of this study was to compare the effect of training breast self-examination by peers and health care personnel on students' knowledge and attitude. Methods: In this quasi-experimental study, 112 students from two schools of dentistry and management of Shiraz University of Medical Sciences were selected randomly and were allocated in two groups. They were taken a pre-test and two post-tests. Data gathering tool was an assessment test evaluating their knowledge about breast cancer and self-examination and their attitude toward breast self-examination. Four or five students from each class were selected and trained as peer instructors. Students of the first group were trained by peers and the students in the second group were instructed by health care personnel separately using booklet. At the end of educational sessions, the first post-test, and after 6 weeks, the second post-test were taken. Statistical analysis was performed using paired t-test and independent t-test, repeated measure ANOVA, and factor analysis test. Results: There was a significant difference between knowledge and attitude scores of the two groups immediately after education, so that, the mean score of knowledge in the group trained by peers was higher than the one educated by health care personnel. But, no significant difference was observed between the attitude scores of the two groups, 6 weeks after education. Comparing the knowledge and attitude scores, before, immediately after and 6 weeks after education showed a significant difference in each group. Conclusion: The efficacy of training breast self-examination by peers is higher than by health care personnel. It is recommended to employ this educational method more, especially in training self-examination.